Remembering, Visiting and Placing the Dead: Law, Authority and Genocide in Srebrenica - O. Simic (Law Text Culture, 2009)
This article addresses the recent development of ‘dark tourism’ in Srebrenica and the blurring between voyeurism and educational enlightenment that such tourism provokes. The article examines the legal and ethical disputes surrounding the authority over the dead who rest in the Srebrenica Cemetery complex. It concludes that while ‘dark tourism’ and the recent law enacted over the complex were intended to secure a reconciliation and respectful remembrance of the dead, they both, to various degrees, have raised serious ethical and legal concerns.